Athanas manticolus sp. nov., a new stomatopod-associated alpheid shrimp from Vietnam (Crustacea, Decapoda) - Ďuriš, Zdenek; Anker, Arthur (Zootaxa, 2014)
A new species of the alpheid shrimp genus Athanas Leach, 1814 is described based on a single specimen, an ovigerous female from Nha Trang Bay, Vietnam. Athanas manticolus sp. nov. differs from all other species of Athanas by the presence of a small post-rostral tubercle, combined with a minutely toothed rostrum, reduced extra-corneal teeth, and the absence of infra-corneal and supra-corneal teeth. In addition, the new species is characterised by its unique colour pattern, particularly by the red chromatophores disposed in randomly oriented, short, narrow streaks. As its name suggests, A. manticolus sp. nov. is commensally associated with the burrows of the nannosquillid mantis shrimp Bigelowina phalangium (Fabricius, 1798).